Blood flow-induced Notch activation and endothelial migration enable vascular remodeling in zebrafish embryos - Bart Weijts (Nature Portfolio, 2018)
The mechanisms of sensing of blood flow and responses to it in vascular remodelling are poorly understood. Here, the authors show that in zebrafish blood flow controls both the fate determination of individual blood vessels and the arterial versus venous identity of endothelial cells lining them.